PENGARUH PENGGUNAAN JENIS ALAT DAN JUMLAH APLIKASI BAHAN BONDING GENERASI KE-7 TERHADAP KEKUATAN TARIK PELEKATAN RESIN KOMPOSIT PADA DENTIN - , NUR AZIZAH; , drg. Diatri Nari Ratih, M.Kes., SpKG., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The present study was undertaken to compare and evaluated tensile bond strength of one step self etch adhesive using multiple coats and different aplicator designs, to dentin premolar maxilla. Flat buccal dentinal surfaces wew obtained on 45 extracted human premolar maxilla. The speciment werw divided into 3 equal groups (n=15). Self etch adhesif wewe applied on the dentinal surface of group I with cotton pellet, goup II with microbrush and group III using brush applicator.The groups were further divided into 3 subgroups-single coats of dentin bonding agent in subgroups A, double coats of dentin bonding agent in subgroups B, and triple coats in subgroup C. The composite was placed on the dentinal surfaces. Tensile Bond Strength was tested for all speciment with universal Testing Machine. Data were statistically analyzed using two way analysis on variance and LSD test. There was statistically significant difference in the main study groups, that is no significant difference in the tensile bonding strength with the use of microbrush and brush applicator. However, the use of double coats of self etch dentin bonding agent exhibhit highly significant difference in tensile bonding strength as compare with single coats and triple coats. This study revealed that double coats with microbrush or brush applicator enhanced the bond strength to dentin owing to the resin infiltration.